1998
DOI: 10.1002/14651858.cd000958
|View full text |Cite
|
Sign up to set email alerts
|

Sulfasalazine for treating rheumatoid arthritis

Abstract: Bacon PA. A double-blind controlled study comparing sulphasalazine with placebo in rheumatoid factor (RF)-negative rheumatoid arthritis..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 19 publications
1
37
0
1
Order By: Relevance
“…The most frequent side eVects responsible for sulfasalazine discontinuation reported in a meta-analysis were gastrointestinal symptoms in 10% and mucocutaneous reactions in 7% [40]. There are conXicting evidence linking acetylator status to toxicity and eYcacy [41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent side eVects responsible for sulfasalazine discontinuation reported in a meta-analysis were gastrointestinal symptoms in 10% and mucocutaneous reactions in 7% [40]. There are conXicting evidence linking acetylator status to toxicity and eYcacy [41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple drug efficacy trials for SSZ have been performed with those for RA often including a primary outcome measure of pain control [20,24]. In a Cochrane report three of six studies reported on pain outcome versus placebo, all three had reduced pain scores with a standardized weighted mean difference of for pain −0.42 (95%CI −0.72;−0.12), test for overall effect: Z = 2.80 (P = 0.0051).…”
Section: Sulfasalazine’s Analgesic Action In Rheumatoid Arthritismentioning
confidence: 99%
“…São contra-indicadas em pacientes que apresentem alterações retinianas e de campo visual (2) (D). b) Sulfasalazina é considerada mais efetiva que o placebo na redução da atividade da doença, no controle da dor e na avaliação clínica global (23) (A). Recentemente, confirmou-se sua eficácia clínica e interferência sobre a progressão radiográfica (24) (A).…”
Section: Drogas Modificadoras Do Curso Da Doença (Dmcd)unclassified